Tracking control of state constrained fractional order nonlinear systems. (April 2022) - Wang, Changhui; Li, Xiao; Cui, Limin; Wang, Yantao; Liang, Mei; Chai, Yongsheng
Abstract: This article investigates adaptive output-feedback control problems for full-state constrained fractional order uncertain strict-feedback systems with unmeasured states and input saturation. By considering the structure of the systems, a fractional order observer is framed to estimate unmeasurable states. By using the backstepping procedure and barrier Lyapunov function, the adaptive controller with adaptation laws are proposed in each step. With the Lyapunov stability theory for fractional order systems, it proves all the states remain in their constraint bounds and the error system converges to a bounded set containing the origin. In the end, Two examples are presented to show the effectiveness of the designed control scheme. Highlights: A constraint control scheme for fractional-order nonlinear systems is developed. Both state constraints and input saturation are considered in the design process. Saturation is approximated by a smooth nonaffine function to overcome nonlinearity. The BLF is employed to satisfy the condition of the state constraints. The proposed scheme guarantees tracking error convergence and boundedness.